Persepsi Guru Terhadap Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah Walisongo Kranji 01 Kedungwuni - Athifah Muzharifah; Irfa Ma’alina; Puji Istianah; Yusmandita Nafa Lutfiah (Concept: Journal of Social Humanities and Education, 2023)
The Merdeka Curriculum is a curriculum with various intra-curricular learning, the content will be more optimal so that students have enough time to explore concepts and strengthen competence. Teachers have the flexibility to choose various teaching tools so that learning can be adapted to the learning needs and interests of students. The purpose of this study was to find out the challenges faced by teachers in implementing the Independent Curriculum at Madrasah Ibtidaiyah Walisongo Kranji 01, Kedungwuni District. The subjects in this study were students at Madrasah Ibtidaiyah Walisongo Kranji 01, while the objects in this study were teachers' perceptions of the implementation of the Independent Curriculum at Madrasah Ibtidaiyah Walisongo Kranji 01. This research was conducted using a type of qualitative research, namely observation and interviews. The results of this study indicate that the teacher's perception of the implementation of the independent curriculum still has difficulties so that it becomes a challenge in implementing the Independent Curriculum at Madrasah Ibtidaiyah Walisongo Kranji 01